Infected urachal cyst in a young adult: A case report - Varshney, Amar; Khanna, Rajesh; Jain, Arvind (Indian Journal of Case Reports, 2020)
The urachal cyst is one of a spectrum of urachal abnormalities most commonly found in children. They are very rarely seen in adults because the urachus is normally obliterated in early infancy. Clinical presentation is non-specific; therefore, a high index of suspicion is required to make the diagnosis. When it is diagnosed, surgical excision is advised due to the risk of malignant transformation. We describe the case of a 26-year-old male who presented with a small swelling of the umbilicus and purulent umbilical discharge. The diagnosis of an infected urachal cyst was confirmed on ultrasonography abdomen and contrast-enhanced computed tomography abdomen. He was treated initially with broad-spectrum antibiotics and then by surgical excision of the cyst and fibrous tract. Histology of the excised specimen showed chronic inflammation with no evidence of malignancy. Post-operative recovery was uneventful.